My mini concert : musical instruments for kids. - Baby Professor (Firm) (Newark, DE : Baby Professor, 2018)
Text and illustrations look at different musical instruments.
"Children's musical instruments."
"Music book for beginners."
6.2
3-6.
3-6
english
Keywords: Musical instruments -- Juvenile literature; Musical instruments; Musical instruments